2023
DOI: 10.3390/agriculture13040778
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Land Use Changes as a Driving Force of Soil Erosion in the Velika Morava River Basin, Serbia

Abstract: The erosion potential model was applied to estimate the soil erosion status of rural settlements during the years 1971 and 2011. We used univariate and bivariate local Moran’s I indices to detect and visualize the spatial clustering of settlements with respect to changes in erosion intensity and agricultural land use, as well as their mutual spatial correlation. The study area was differentiated into four statistically significant clusters using the calculated bivariate local Moran’s I indices. The statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 90 publications
1
3
0
Order By: Relevance
“…In a study [103], it was found that 55.20% of the Kratovska Reka catchment exhibits low erosion rates, whereas the majority of the Štrpce municipality (50.03%) displays low erosion rates. Similar observations have been made by studies conducted by [38,45,104], which indicate that the intensity of soil erosion is closely linked to dynamic interactions among natural conditions, demographic and settlement indicators, and changes in land use.…”
Section: Discussionsupporting
confidence: 83%
“…In a study [103], it was found that 55.20% of the Kratovska Reka catchment exhibits low erosion rates, whereas the majority of the Štrpce municipality (50.03%) displays low erosion rates. Similar observations have been made by studies conducted by [38,45,104], which indicate that the intensity of soil erosion is closely linked to dynamic interactions among natural conditions, demographic and settlement indicators, and changes in land use.…”
Section: Discussionsupporting
confidence: 83%
“…Most studies conducted in Serbia and the wider region show that in addition to the implemented erosion control measures, demographic changes in the watershed also had a significant impact on reducing soil erosion intensity, primarily due to the decrease in population and unfavorable age structure [23,24,27,69]. All of this has led to a reduction in agricultural production, resulting in the formation of grassland and forest cover on abandoned fields and orchards through the spontaneous growth of vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies on the effects of erosion control works at the national, regional [23][24][25][26][27][28] and global levels indicate their significance in reducing soil erosion intensity [29][30][31][32][33]. Technical works provide the desired results in a shorter time period, while biological and biotechnical works provide a long-lasting solution to erosion and sedimentation issues within the watershed.…”
Section: Introductionmentioning
confidence: 99%
“…Although the rapid expansion of construction land may reduce soil loss in the short term, this phenomenon is neither positive nor sustainable [71]. The expansion of construction land often involves converting natural surfaces such as forests and grasslands into hard structures like buildings and roads, which reduces the likelihood of soil weathering or erosion but also deprives the land of its original ecological value [72]. Ecosystem services provided by natural surfaces, such as maintaining biodiversity, regulating the water cycle and climate, and promoting soil nutrient cycling, are significantly reduced after the expansion of construction land, thereby causing long-term negative impacts on the environment [73].…”
Section: Future Soil Erosion Control Strategiesmentioning
confidence: 99%